2021
DOI: 10.1097/md.0000000000026289
|View full text |Cite
|
Sign up to set email alerts
|

Effects of atorvastatin on the insulin resistance in women of polycystic ovary syndrome

Abstract: Background: Atorvastatin treatment has been suggested as a therapeutic method for women with polycystic ovary syndrome (PCOS) in many clinical studies. Nonetheless, the effects of atorvastatin on insulin resistance in PCOS patients still remain controversial. Objective: The aim of this report was to evaluate the effects of atorvastatin therapy on the insulin resistance in the treatment of PCOS compared to that of placebo, in order to confer a reference for clinical prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…In this investigation, atorvastatin dramatically decreased acylation stimulating protein (ASP), IL-6, and monocyte chemoattractant protein-1 (MCP-1), which are markers of inflammation and adipose tissue dysfunction, followed by a significant improvement in HOMA-IR and testosterone levels [ 105 ]. In randomized placebo-controlled research, atorvastatin significantly decreased hyperandrogenism, inflammatory markers, and insulin resistance in PCOS-affected women compared to a placebo [ 106 , 107 ]. A measure of oxidative stress, serum malondialdehyde (MDA), was dramatically lowered in obese women with PCOS receiving atorvastatin treatment [ 108 ].…”
Section: Emerging Therapeuticsmentioning
confidence: 99%
“…In this investigation, atorvastatin dramatically decreased acylation stimulating protein (ASP), IL-6, and monocyte chemoattractant protein-1 (MCP-1), which are markers of inflammation and adipose tissue dysfunction, followed by a significant improvement in HOMA-IR and testosterone levels [ 105 ]. In randomized placebo-controlled research, atorvastatin significantly decreased hyperandrogenism, inflammatory markers, and insulin resistance in PCOS-affected women compared to a placebo [ 106 , 107 ]. A measure of oxidative stress, serum malondialdehyde (MDA), was dramatically lowered in obese women with PCOS receiving atorvastatin treatment [ 108 ].…”
Section: Emerging Therapeuticsmentioning
confidence: 99%
“…This current meta‐analysis showed that statins treatment could lower fasting glucose and insulin sensitivity index in women with PCOS. However, Chen et al reported that atorvastatin therapy was associated with reduced fasting insulin level and HOMA‐IR, while no relationship was found between atorvastatin and fasting glucose level 25 . A meta‐analysis published by Meng et al showed no obvious impact on fasting glucose between metformin alone and combination treatment of simvastatin and metformin 26 .…”
Section: Discussionmentioning
confidence: 99%
“…However, Chen et al reported that atorvastatin therapy was associated with reduced fasting insulin level and HOMA-IR, while no relationship was found between atorvastatin and fasting glucose level. 25 A metaanalysis published by Meng et al showed no obvious impact on fasting glucose between metformin alone…”
Section: Discussionmentioning
confidence: 99%
“…The influence on transcriptional activity was less evident and reached statistical significance in cells exposed to high atorvastatin concentration, which might reflect a potential influence on posttranslational modifications inflicted by statin exposure. Human in vivo studies give conflicting results on the subject, showing reduced insulin expression during atorvastatin therapy in patients with polycystic ovary syndrome (Chen and Zheng, 2021), or lack of negative impact on insulin concentration in hyperlipidemic subjects (Buldak et al, 2012). Whereas fluvastatin therapy was associated with increased insulin levels and increased insulin resistance in healthy volunteers (Felder et al, 2021).…”
Section: Discussionmentioning
confidence: 99%